1983
DOI: 10.2307/3281059
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transmission of Asexually Proliferative Mesocestoides corti Tetrathyridia (Cestoda) in Mice

Abstract: Asexually proliferative Mesocestoides corti tetrathyridia were studied to test the hypothesis of in utero transmission in mice and define more clearly the path of transmammary transmission. In utero transmission was not observed in 132 fetuses (22 litters) taken by caesarean section from infected mothers. However, 19 of these mothers had tetrathyridia in their mammary glands at the time of operation, nine had worms in the uterine lumen, and one had a single worm in the maternal blood space of a placenta. No te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…corti tetrathyridia have been largely used as a cestode experimental model, especially in immunobiology, biochemistry, pharmacology, and physiology of these parasites (Chernin and McLaren, 1983;Conn and Etges, 1983;Williams and Conn, 1985;Terenina et al, 1995;Kadian et al, 1996;Cardona et al, 1999).…”
mentioning
confidence: 97%
“…corti tetrathyridia have been largely used as a cestode experimental model, especially in immunobiology, biochemistry, pharmacology, and physiology of these parasites (Chernin and McLaren, 1983;Conn and Etges, 1983;Williams and Conn, 1985;Terenina et al, 1995;Kadian et al, 1996;Cardona et al, 1999).…”
mentioning
confidence: 97%
“…Posterior end of the same aberrant tetrathyridium in Fig. 7 showing clusters of abnormal branching tegumental pits (Tp) but normal posterior excretory antrum (E) laboratories around the world (Conn and Etges 1983;Williams and Conn 1985;Conn 1990;Etges 1991). Asexual reproduction of Mesocestoides tetrathyridia by mechanisms other than fission of the scolex, such as fission or budding of the hindbody, is much more common and has been reported from a variety of hosts from various parts of the world.…”
Section: Discussionmentioning
confidence: 98%
“…But the story does not stop here. Experiments by Conn and Etges (1983) have shown that tetrathyridia can also be transmitted from mother to suckling mice via the transmammary route. This pattern of transmission, more common in nematodes and trematodes (Miller, 1981;Shoop, 1988), is apparently not rare since up to 62% of young nursing mice were infected this way.…”
Section: Commentsmentioning
confidence: 97%